Platelet reserve of Epidermal Growth Factor: approach to a possible emerging concept - Pérez Hernández, Héctor José; MacÃas Abraham, Amparo (MEDISAN.., 2024)
Introduction: Epidermal growth factor precursor is immersed in the context to Platelets membrane. The regular procedure to obtain serum implies a barrier to biological understanding of the theoretical meaning of its values. Objective: To describe the effect to modified procedure to measure sample epidermal growth factors and the possible biological implications for this. Method: An in vitro experimental study was carried put, with blood samples from individuals with apparent health history, in adulthood. Serum epidermal growth factor precursor values were determined with the UMELISA-EGF kit recommended by the manufacturer; the experimental variation in sample collection was carried out according to SAMERSAC recommendations for platelet-rich plasma, with adjustments. Results: The average age was 45.89± 3.35 years, in a range of 27 to 62 years. The female sex predominates in a 1.8:1 ratio. Application of the experimental procedure showed significant and notable differences between the epidermal growth factor values (g=17.7; p=0.0001-23); no linear correlation was evident between the values (r= 0.1305; p= 0.6843). The "reserve" value was on average 1498.61 ±160.68 pg*mL-1, observing large effect differences, as well as a similar behavior to a transition value. The observed data suggest, a posteriori, consumption effect on the course of platelet lysis under standard conditions. Conclusions: Epidermal growth factor values are higher after platelet isolation; the existence of an intraplatelet reserve of epidermal growth factor is plausible.